MENGEMBANGKAN KEMITRAAN PENGELOLAAN SUMBER DAYA AIR DI DUKUH KALIURANG DESA KEMBANGLANGIT KEC. BLADO KAB. BATANG - Agus Fakhrina; Maghfur; Musoffa Basy (JURNAL PENELITIAN, 2012)
This study was aimed: (1) to map socio-economic situation in Kaliurang, (2) to identify the issues that were most felt by the community living in Kaliurang, (3) to know the impact of socio-economic after the water source ìSigintungî controlled by the Municipal Waterworks (PDAM) of Batang Regency, (4) to encourage the initiation to build partnership management of water resources between the community and the stakeholders in Batang, and (5) to obtain alternative management schemes that guarantee the rights of local communities with stakeholders in realizing fair and sustainable management of water resources. The approach taken in this study were: (1) Rapid Rural Appraisal, (2) Participatory Rural Appraisal, and (3) Participatory Action Research. The result of this research shows that the controlling water source ìSigintungî by PDAM bring about apprehensive impact to the local community so that they live in poverty, and this is the issue that is most felt by them. Therefore, they want to solve this problem by initiating partnership management of water resources between them and the stakeholders in Batang, and the result is that now, they can access the water from the PDAM's water receptacle in water source "Sigintung" directly. In addition, they build water installation and receptacle beside the Musholla to transport water from the receptacle to their houses, even though other expectation cannot be realized due to the stakeholders attending the meeting in Kaliurang were not the managements that can make a decision.